Contribution eye studying education citizenship to formation character students at the Faculty Tadulako University livestock and fisheries - Fatmawati; Herlina; Hasan (Kirana Publisher (KNPub), 2024)
Citizenship Education in universities tall expected can become vehicle development character student individually which in turn will accumulate become character dignified nation . The problem is How formulate development character nation it's in the middle Indonesia's multicultural society and how it works in practice learning eye studying Citizenship Education at college the best height done For development character nation . Formulation problem from study This that is What is the learning process like? eye studying education citizenship in form character student Faculty Tadulako University Livestock and Fisheries , contribution material education citizenship to formation character student Faculty Tadulako University Livestock and Fisheries . As for goals from study This that is For understand the learning process in the eye studying education citizenship in form character student Faculty Tadulako University Livestock and Fisheries For know material education citizenship to formation character student Faculty Tadulako University Livestock and Fisheries . Research methods used by researchers that is study qualitative . Result of study This that is formation character Basically in matter this one has not quite enough answer For form character nationalism is learning Pancasila Education, because character nationalism is something the value contained within Pancasila principles , namely the unity of Indonesia.